AUTOMATIC VALVE SLUICE GATE DESIGN MADE OF FIBERGLASS IN TIDAL AGRICULTURAL AREA - Wardana, Alifia Ayu; Lestari, Arfena Deah; Meirany, Jasisca; Danial, Mochammad Meddy; Supriyadi, Asep (Fakultas Teknik Universitas Tanjungpura, 2023)
Water control technology aims to provide a sufficient water supply to avoid overflow. An automatic valve sluice gate made from fiberglass is preferred for water control in tidal agriculture. The mechanical valve sluice gate model can automatically release and close water discharge at a precise angle to optimize water control in tidal agriculture. The advantage of this sluice gate design is its utilization of the difference between upstream and downstream water levels on the sluice gate. A sluice gate design with a slope angle of 15 ° is recommended for tidal agriculture. The upstream water level should reach a height of 1.67 m for the sluice gate to open, while the downstream side should be at 0.82 m. The sluice gate will automatically open if the water level difference is 0.85 m in height and close if there is no water level difference. It is known that the flood level from the ground is 1 m to 2 m. It is suggested to elevate the land to prevent flooding for residents.